Determinasi Pengambilan Keputusan Kolaboratif Kepala Sekolah Di Smp Swasta: - Susanto, Teguh Trianung Djoko; Ramadhan, Nabil Auliya; Sari, Nirwana Nilam (Universitas Pakuan, 2025)
PRINCIPAL DECISION-MAKING DETERMINATION IN THE PRIVATE EDUCATIONAL INSTITUTION SMP TERPADU PRIMA BANGSAThis study aims to explore the decision-making process of the principal at SMP Terpadu Prima Bangsa, identify the influencing factors, and analyze its implications for school management and performance. A qualitative approach with a case study method was employed to investigate the dynamics of decision-making within the context of a private educational institution. Data were collected through field observations, in-depth interviews with the principal, vice principals, and teachers, as well as visual documentation in the form of photographs related to the implications of decision-making at SMP Terpadu Prima Bangsa. The data were then analyzed using Miles and Huberman’s interactive model through data reduction, data display, and verification. Triangulation techniques were used to ensure data validity. The findings indicate that the principal’s decision-making process is collaborative, transparent, and data-driven, involving various stakeholders within the school environment. Although the final decision rests with the principal, the process reflects a participatory organizational culture and emphasizes continuous evaluation. The decisions made are strategic, taking into account educational ideals, operational conditions, and the foundation’s policies. The principal demonstrates reflective and adaptive leadership capable of responding contextually to the dynamics of education. These findings suggest that effective decision-making has a significant impact on improving school management, collaborative work culture, and the quality of educational services.